Encountering shame and guilt - Green, Daniel R.; Lawrenz, Mel (Grand Rapids, MI Baker, 1994)
Includes bibliographicaol references.
Keywords: Pastoral counselling; Shame -- religious aspects -- Christianity; Guilt -- religious aspects -- Christianity